Jewish stories of wisdom - Fischmann, Patrick (Black Dog & Leventhal Publishers, 2016)
"An illustrated keepsake collection of old-world Jewish tales of faith and morality. Beautifully packaged with a cloth case, foil stamping, a ribbon book marker, and lush full-color artwork on every page. Jewish Stories of Wisdomis the perfect antidote to our busy, modern lives. It serves as a daily companion that one can return to again and again for a much-needed moment of spiritual sustenance. The 34 stories in this uplifting collection can be read in solitude or shared with others. Among them are "The Poet and the Pirate," "The Language of the Kings," "The Laughter of the Light," "The True Beauty," and many others. Patrick Fischmann is a writer whose work is to gather stories from around the world for a multicultural and spiritual awakening. He is the author of dozens of titles including several in the Contes des Sages series published by Editions du Seuil in France. He is a storyteller, singer, and multi-instrument songwriter. He lives in France"--Provided by publisher